Self-Control as a Criminogenic Need: A Longitudinal Test of Social Intervention to Improve Self-Control - R. C. Morris (Russian Journal of Economics and Law)
Objective: to study the notion of self-control as the main factor of criminogenic needs and criminal behavior.Methods: dialectical approach to cognition of social phenomena using the general scientific (analysis, synthesis, induction) and specific scientific (formal-legal, systemic, comparative-legal, sociological) research methods.Results: the study addresses the theoretical debate between psychogenic and sociogenic arguments of anti-social behavior. The psychogenic arguments defining self-control found in the general theory of crime get compared to the sociogenic assumptions of social control theory. This paper frames self- and social control as two sides of the same social psychological coin, suggesting that key value-identities represent the core of selfcontrol. A year of panel data were gathered from 173 children participating in a community-based mentoring program. Of key interest, this study provides an analysis of children facing acute risk for anti-social outcomes, including a group of children impacted by parental incarceration.Scientific novelty: the work substantiates that self-control varies along different trajectories for different children across a year of social intervention, questioning the relative stability assumption in self-control theory. Children unimpacted by parental incarceration experience increases in self-control across a year of mentoring while children impacted by parental incarceration experience declines in self-control. Results suggest that social intervention programs serving children at-risk for intergenerational crime need to take a cue from clinical treatment models targeting criminogenic needs.Practical significance: the main provisions and conclusions of the article can be used in scientific, pedagogical and law enforcement activities when considering issues related to the crime prevention and suppression.